2022
DOI: 10.1101/2022.02.23.481681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enrichment of somatic mutations in schizophrenia brain targets prenatally active transcription factor bindings sites

Abstract: Schizophrenia (SCZ) is a complex neuropsychiatric disorder in which both germline genetic mutations and maternal factors, such as infection and immune activation, have been implicated, but how these two strikingly different mechanisms might converge on the same phenotype is unknown. During development, cells accumulate somatic, mosaic mutations in ways that can be shaped by the cellular environment or endogenous processes, but these early developmental mutational patterns have not been studied in SCZ. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 67 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…12 By the whole-genome sequencing (WGS) approach, a comprehensive study reported no significant difference in the somatic mutation burden between patients with SZ and controls (CTs), 13 while another study reported an increased number of sSNVs with altered mutation signatures in the neurons of patients with SZ. 14 Considering the immaturity of this field, more studies with different perspectives should be performed to understand the role of somatic mutations in the cause of SZ. In addition, the findings should be complemented with cellular and animal model studies, which have rarely been conducted thus far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 By the whole-genome sequencing (WGS) approach, a comprehensive study reported no significant difference in the somatic mutation burden between patients with SZ and controls (CTs), 13 while another study reported an increased number of sSNVs with altered mutation signatures in the neurons of patients with SZ. 14 Considering the immaturity of this field, more studies with different perspectives should be performed to understand the role of somatic mutations in the cause of SZ. In addition, the findings should be complemented with cellular and animal model studies, which have rarely been conducted thus far.…”
Section: Discussionmentioning
confidence: 99%
“…12 These inconsistencies may be due to differences in DNA sequencing and analytical procedures as well as differences in the tissues used in each study. In particular, one WGS study reported a 15% increase in sSNVs in neurons of an SZ group compared with a CT group, 14 indicating that somatic mutations can accumulate in the intragenic regions, which cannot be assessed by WES.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Current estimates attribute 5-10% of the missing genetic heritability of more than 100 human disorders to somatic mutations (Yang et al, 2020). Somatic mutations are a known cause of, or have been implicated in several brain disorders from developmental neuropsychiatric disorders such as focal epilepsy, autism spectrum disorders (ASD) and schizophrenia (SCZ) to neurodegeneration and Alzheimer's disease (AD) (Lim et al, 2015;D'Gama et al, 2017;Lim et al, 2017;Winawer et al, 2018;Baldassari et al, 2019a,b;Rodin et al, 2021;Sherman et al, 2021;Maury et al, 2022;Miller et al, 2022).…”
Section: Somatic Mosaicism In Neuropsychiatric and Neurodegenerative ...mentioning
confidence: 99%
“…A separate study also showed a significant contribution of large (>4 Mb) CNVs to ASD risk in 0.2% of probands (Sherman et al, 2021). Somatic mutation contribution to SCZ has been explored through deep WGS of purified neuronal populations, which identified two mechanisms contributing specifically to SCZ compared to control neurons, referred to as "skiagenesis" (Maury et al, 2022). A significant increase in sSNVs proximal (+/−1 Kb) to the midpoint of active transcription factor binding sites (TFBS) was observed, with enrichment seemingly related to fetal development but not brain-specific.…”
Section: Somatic Mosaicism In Neuropsychiatric and Neurodegenerative ...mentioning
confidence: 99%